Development of Instagram reels-based teaching materials for zero-waste pattern-cutting in fashion design training centers - Prihatin Prihatin; Achmad Noor Fatirul; Harwanto Harwanto (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
As an effort to align learning at fashion design training centers with industry needs and the huge potential of Instagram reels as an innovative learning medium in the digital era, this research aims to evaluate the effectiveness of Instagram Reels as a learning medium for making fashion patterns using zero-waste pattern-cutting techniques at fashion design training centers. Using the Dick and Carey model of research and development (R&D) approach, this research lasted for four months involving three expert validators (material, media, design), three peers, six fashion design training centers, and 49 students at different learning levels. The research results show that teaching materials based on Instagram Reels meet the validity criteria and have a positive response of 88.35% from expert validators and peers. The percentage of product suitability assessments from user/student respondents was 75.9%, indicating that this teaching material is suitable for widespread application in learning. This research contributes to providing an innovative learning approach that increases students' interest, understanding, practical skills, and creativity in mastering the concept of zero-waste pattern-cutting design and providing solutions to challenges in learning fashion design and reducing waste in the fashion industry.